Clinical features of the flow of serous and purulent meningitis - Zadiraka D. А.; Ryabokon, O. V. (Zaporozhye Medical Journal, 2013)
We show that the feature of the clinical symptoms of serous and purulent meningitis is a frequent dissociation of meningeal signs, the most pronounced in serous meningitis (62.1 vs. 30.4%). Difficulty deciphering the etiologic diagnosis is confirmed by the low level of detection of the etiologic factors: in purulent meningitis etiology confirmed in 52.1% of cases, and in serous only 13.7%.